Reconstructing the Qur’anic Concept of Corruption: Amin al-Khulli’s Semantic Approach to Ghulūl, Risywah, and Suḥt - Nurhaliza Oktaviani Z; Zubair Zubair (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2025)
In describing the concept of corruption, the Qur'an does not explicitly mention it but uses several terms such as ghulūl, suḥt, and sariqah. Risywah is not a term of the Quran but an act of bribery whose behavior is explained in the Quran. This research aims to reconstruct the meaning of corruption in the Quran through two steps of semantic analysis by Amin al-Khulli, namely: dirasah ma hawla al-Quran which examines the context of the research object and dirasah ma fi al-Quran which examines the content of the research object. This research is qualitative with two stages of analysis to achieve a complex explanation sourced from literature materials. Through thematic methods in classical and contemporary interpretation, this study reveals the development of the meaning and concept of corruption in the Quran. The results of this study show that the concept of corruption from time to time has adjustments to the context of the times. Islam is adaptive to problems that have occurred from the past to the present. Ghulūl, which is interpreted as embezzlement of war spoils, develops into an abuse of power and embezzlement of funds. Risywah is not only related to the court system but extends to economic, business and social systems. As for suḥt, it is a general form of the act of eating haram treasure which includes the proceeds of bribery and embezzlement of funds. The reconstruction of this concept reveals that corruption is the act of eating property illegally, which can kill the heart from distinguishing right and wrong. So that corruption can cause new problems from the inability of humans to judge a case properly because the perpetrators have been obscured by bribes, as well as damaging the legal order which results in human morality and integrity